Justiça e Comunicação: o diálogo (im)possível ("Justice and communication: the (im)possible dialogue") - Carlos Camponez (Documentos, 2013)
The growing porosity of the boundaries between the justice system and the media should be considered with reference to the demands of the present age. It is difficult for contemporary societies to deal with a justice system that is closed in upon itself and oriented by a strict rationality. They demand more scrutiny of judicial decisions, clearer and more transparent discursive practices, and more accountability to the public and the media. However, these societies do not have any structure for mediating social reality and the formation of communicative opinion, which means that the communicational exchanges that take place in the various fields of collective life are amplified by being managed within a broad public area and used to construct a multiplicity of relations.ALT_QUEBRA_LINHADespite the areas of tension involved, the justice system and the media are, we believe, in a position to foster a better understanding, not only on a normative level, given the public responsibilities accruing to both institutions in contemporary democracies, but also empirically, as this book attempts to show. In fact, by stimulating reflection about the boundaries that join and separate the different levels of formal public deliberation, as represented by the courts, and the informal level represented by the media, this collection of texts manages to redeem the traditional theorization in this domain from a revived scepticism.